Evaluation of the Operational Performance of School Buses (Trans Pontianak Buses) in Pontianak City - Rizal Rizal; Satrio Utomo; Nernawani Nernawani; Asmadi Asmadi (Journal of Social Research, 2025)
The city of Pontianak as the capital of West Kalimantan Province is growing. But along with these developments, various problems have arisen in various aspects. One of the examples that needs to be resolved immediately is the issue of transportation. This field has quite complex problems. The number of private vehicles is increasing every year. It has an impact on the smooth transportation system in this city. Extraordinary traffic jams often occur at a number of points at certain times. This research consists of several stages. The stages in this study are the identification of the operational performance of school buses, potential problems and passenger perceptions, collecting primary data and secondary data in the study area by conducting interviews and distributing questionnaires, as well as requesting data from related agencies, and the last step is to draw conclusions in accordance with the formulation of the problem from the results of analysis and discussion. From the results of the research conducted to evaluate the operational performance of school buses, the results were obtained that the performance of school buses in Pontianak City can be seen from the load factor value of less than 1 for all segments, showing that the capacity of school buses is still met for school bus users, from the results of direct observation in the field, the travel time of the trans pontianak bus is 30-45 minutes there is no need to wait a long time to get to their respective schools, The positive things related to the operation of this school bus are safety, comfort, punctuality and cost savings for students who use the vehicle, and several weaknesses and threats were found to the operation of the Trans Pontianak Bus, one of which is the lack of interest of students to use the Trans Pontianak bus.